A Preliminary Study of Arecoline and Guvacoline Presence in the Saliva of a "Betel-Quid" Chewer Using Liquid-Chromatography Ion Trap Mass Spectrometry. Issue 5 (October 2013) - Kadi, Adnan A.; Attwa, Mohamed W.; Rahman, A.F.M. Motiur
It has been reported that the parasympathomimetic alkaloid arecoline and the nootropic agent guvacoline have been detected in areca nut ( Areca catechu L.) during extraction using a basic medium. Here, we have studied the detection of arecoline and guvacoline in vivo in saliva of a "betel-quid" chewer using liquid-chromatography ion trap mass spectrometry. In this paper, we provide evidence that guvacoline is absent in the neutral aqueous extract of betel nut, but is present in abundance in the aqueous extract with added lime (pH 11.9). In an in vivo experiment, we demonstrated that guvacoline is present in the salivary extracts in the mouth with lime (pH 9.5) and without lime (pH 5.3).